Structural diversity in medicinal plants: Identification and quantitative analysis of secondary metabolites using HPTLC and LC-MS for determining its anti-inflammatory activity - SHAIKH, AJAM C; Gupta, Amit; CHAPHALKAR, SUSHAMA R (Innovare Journal of Agricultural Sciences, 2017)
One of the complex pathophysiological process i.e. inflammation (acute or chronic), which is mediated by a variety of signaling molecules. Lot of anti-inflammatory drugs (synthetic based origin) that are available but some of them are no longer use due to its side effects. Recently, people relied on various medicinal plant products especially leaves pertaining to secondary metabolites. In the present study, our group focused on various medicinal plants i.e. Prosopis spicigera, Anthocephalus cadamba, Mangifera indica and Madhuca indica in order to identified (qualitatively), isolated (quantitatively) and determined its secondary metabolites that are present in the aqueous leaves extract. The results of these studies showed that these secondary metabolites that are present in aqueous leaves extract showed wide variation in phytochemicals qualitatively and quantitatively using high performance thin layer chromatography (HPTLC) and also observed some variations in molecules identified through liquid chromatography mass spectrometry (LC-MS) as well. In addition, variable concentration of aqueous leaves extract of Prosopis spicigera, Anthocephalus cadamba, Mangifera indica and Madhuca indica when exposed to lysed human whole blood in presence of Concanavalin (Con)-A Â and the results showed that aqueous leaves extract showed anti-inflammatory activity against Con A at higher doses.